Prevalence, severity of scabies, and relationship between gender and education level with scabies disease in Pesantren X Wonosobo - Putranti, Ismiralda Oke; Suryani, Luluk Kharisma; Safitri, Lutfi Aulia (Jurnal EduHealth, 2024)
Scabies is a common skin disease caused by infection of Sarcoptes scabiei, which is transmitted directly human-to-human contact, especially in crowded community like pesantren. The purpose of this study was to determine the prevalence, and association between scabies with gender and education level of students in Pesantren X Wonosobo. This cross-sectional study was conducted to all students (238 students) in 2023. Diagnosis was made based on anamnesis and dermatology examination. Data were analyzed using chi square test. The results showed that the prevalence of Scabies was 78,15% (male 83,1% and female 63,9%; education level tsanawiyah 84,5% and aliyah 44,73%). and the severity of scabies was moderate level (64%). Chi square test showed significant difference between the prevalence of Scabies with gender (p=0.002) and education level (p=0.003) of the students. In conclusion, the prevalence of Scabies in Pesantren X Wonosobo was 78,15 %. There was association between the prevalence of Scabies with gender and education level of students.